ExoMol line lists – L: high-resolution line lists of H3+, H2D+, D2H+, and D3+. Issue 4 (9th January 2023) - Bowesman, Charles A; Mizus, Irina I; Zobov, Nikolay F; Polyansky, Oleg L; Sarka, János; Poirier, Bill; Pezzella, Marco; Yurchenko, Sergei N; Tennyson, Jonathan
ABSTRACT: New MiZo line lists are presented for the D2 H + and D$_3^+$ isotopologues of H$_3^+$ . These line lists plus the existing H$_3^+$ MiZATeP and the ST H2 D + line lists are updated using empirical energy levels generated using the marvel procedure for H$_3^+$, H2 D +, and D2 H +, and effective Hamiltonian energies for D$_3^+$ for which there is significantly less laboratory data available. These updates allow accurate frequencies for far infrared lines for these species to be predicted. Assignments of the energy levels of H$_3^+$ and D$_3^+$ are extended using a combination of high accuracy variational calculations and analysis of transition intensities. All line lists are made av ailable via www.exomol.com .